BUSINESS STRATEGY WITH BUSINESS MODEL CANVAS (BMC) AND SWOT ANALYSIS ON COTO MAKASSAR LAO MANRE MSME - Hadi Saputro, Edwin Dwi Kusdantoro; Fatra, Nargadias; Yudagara, Enggar Pandu; Alfatunnisah, Anna; Al Hafri, Shahnur; Aprilianto, Flavio; Cahya, Agus Dwi; Fauzi, Fitriya (SMARTINDO, 2024)
This community service activity aims to provide education to business owners through mentoring Micro, Small and Medium Enterprises (MSMEs) by discussing business strategies through the Business Model Canvas (BMC) approach and SWOT Analysis (Case Study on Coto Makasar Lao Manre). This strategy also applies the teachings of Ki Hajar Dewantara, namely “Ing Madya Mangun Karsa”. The results of observations and interviews that have been carried out show that UMKM Coto Makasar Lao Manre has intense competition among culinary business actors. Therefore, the community service team provides training related to the Business Model Canvas (BMC) approach strategy and SWOT Analysis. The purpose of this training is expected to help Coto Makasar Lao Manre Micro, Small and Medium Enterprises (MSMEs) to compete and continue to grow.